Pelaksanaan Pastoral Sekolah di SMP Katolik Dan SMP Negeri Kota Malang - Yohanes Chandra Kurnia Saputra (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2022)
As far as the writer observed, the students experienced an identity crisis and weak self-control eventually caused the students to often fall into negative things. Such as promiscuity, drinking, brawls, pornography, free sex, and so on. Such a crisis is expected by the Church to be overcome by pastoral schools. Pastoral schools aim to develop, improve and foster students' faith lives. But in reality, there are still many schools, both public and private, that have not implemented school pastoral well. This study aims to determine the implementation of pastoral schools in the Catholic and State Junior High Schools of Malang City and its impact on the development of students' faith and morals. Is the better the pastoral implementation of the school, the better the faith and moral development of students? Through the quantitative method with the Independent T-Test formula combined with the qualitative method, we conducted research in two Catholic Junior High Schools and two State Junior High Schools with a sample of 48 students. The results showed that the implementation of pastoral care at the Catholic Junior High School in Malang City was better than at the State Junior High School. But the implementation of a good school pastoral is not directly proportional to the students' faith and moral development. Good pastoral practice does not necessarily guarantee the faith and moral development of students. It is proven between Marsudisiwi Catholic Middle School and Sta. Maria was not significantly different where the content obtained was 0.915 with a significance of 0.368. While SMP Catholic Middle School Sta. Maria with SMP Negeri 5 and SMP Negeri 3 was significantly different where the count obtained was 4,940 with a significance of 0.000. Meanwhile, the results of the interviews showed that the faith and moral development of students in Catholic Junior High Schools was not better than that of State Junior High School students.